Energy transfer-enabled enantioselective photocyclization using a privileged Al-salen catalyst - Soika, Julia; Onneken, Carina; Wiegmann, Thorben; Stünkel, Timo; Morack, Tobias; Lindfeld, Leander; Hebenbrock, Marian; Mück-Lichtenfeld, Christian; Neugebauer, Johannes; Gilmour, Ryan (Nature chemistry, 2025)
Chiral catalysts that can engage multiple substrates, via distinct ground-state activation modes, to deliver enantioenriched products with high levels of fidelity are often described as ‘privileged’. Achieving generality in excited-state processes remains challenging, and efforts to identify privileged chiral photocatalysts are being intensively pursued. Aluminium-salen complexes are emergent contenders on account of their well-defined photophysical properties. Here we report the development of an enantioselective energy transfer (EnT) catalysis-enabled photocyclization of acrylanilides to expand the activation repertoire of Al-salen photocatalysts. This approach allows reactivity and enantioselectivity to be simultaneously regulated by an inexpensive, commercial chiral Al-salen complex upon irradiation at λ = 400 nm. Diverse cyclic products can be forged with high levels of enantioselectivity (up to 96:4 e.r.). Establishing this dichotomy in excited-state activation modes serves to consolidate the privileged status of chiral Al-salen complexes in enantioselective photocatalysis and to complement their ubiquity in ground-state regimes.
Online veröffentlicht: 17. Juli 2025
Gesehen am 18.11.2025